Mystery of the glowing eye. - Keene, Carolyn (Nancy Drew mystery stories, 51, 1974)
A fiery glowing eye in a museum, the abduction of Ned, the code name Cyclops, and a pilotless helicopter draw Nancy and her friends into a dangerous investigation.